2016
DOI: 10.22359/cswhi_7_2_07
|View full text |Cite
|
Sign up to set email alerts
|

Mobbing experienced by nurses in health care facilities

Abstract: Abstract:The article deals with the issues of mobbing in health care facilities. Nurse is one of the professions excessively exposed to the mobbing behaviour. Compared to other sectors, the risk of occurrence of this negative phenomenon in health care sector is up to seven times higher. The empirical part of the paper includes an analysis and a comparison of the results of the research carried out as a descriptive study with the aim to determine the extent to which mobbing is experienced by nurses, its emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Neuroticism was also associated with harassment. Our literature review detected only one similar study in Slovak nurses [ 31 ], but the authors did not find any relationship between neuroticism and mobbing (although they used their own mobbing questionnaire). When we looked at this relationship in other types of samples, we found contradictory results.…”
Section: Discussionmentioning
confidence: 89%
“…Neuroticism was also associated with harassment. Our literature review detected only one similar study in Slovak nurses [ 31 ], but the authors did not find any relationship between neuroticism and mobbing (although they used their own mobbing questionnaire). When we looked at this relationship in other types of samples, we found contradictory results.…”
Section: Discussionmentioning
confidence: 89%
“…The results of a study conducted by Jerng et al ( 26 ) showed that interpersonal conflicts among healthcare workers can negatively affect their well-being, and this is in line with the results of the present study, which showed that nurses experience non-cooperation and tension created by some other nurses. To improve collaboration among nurses and reduce interpersonal conflicts, healthcare organizations should create a supportive work environment, provide clear rules and procedures to prevent negative behavior, and promote mutual respect among healthcare workers ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Las consecuencias para las víctimas pueden ser variadas; a nivel organizacional se describe una menor satisfacción laboral, aislamiento, disminución de la creatividad e innovación, absentismo, disminución de la concentración, aumento de la tasa de renuncia e incremento de los accidentes laborales (Divincová y Siváková, 2014;Zacharová y Bartošovič, 2016;Vveinhardt y Sroka, 2020). A nivel personal, el acoso genera sensaciones de cansancio y estrés, dolores de cabeza, sueño irregular, frustración, apatía, hipersensibilidad, irritabilidad, infravaloración, aislamiento, depresión (Ovayolu y cols., 2014).…”
Section: Acoso Laboralunclassified